KAJIAN LITERATUR TREN PENELITIAN PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN CANVA PADA RENTANG TAHUN 2020-2025 - Wildan Qosid Ilahy; Bambang Subali; Nuni Widiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of technology in the education sector encourages innovation in The advancement of interactive learning media, including the use of Canva as a tool in the learning process at various levels. This literature review aims to analyze research trends related to the development of interactive learning media assisted by Canva in the period 2020–2025. This research applies a literature study method by reviewing various scientific articles, proceedings, and related research reports. The study findings indicate that the utilization of Canva in learning at various levels is increasing, especially in increasing student engagement, teacher creativity, and the effectiveness of material delivery. In addition, the study also shows that Canva has advantages in ease of access, design flexibility, and the ability to support various student learning styles. However, its implementation faces several challenges, including limited access to digital devices and the need for training for teachers. In conclusion, the use of Canva as an interactive learning media has great potential In enhancing the quality of education at various levels, but infrastructure support and training are needed for educators so that its implementation is more optimal. According to the findings of the MOST analysis, there are certain shortcomings in The creation of interactive learning media utilizing Canva. Some of them are the lack of support for independent learning without teacher assistance, the need for additional technology to access the media, and the development carried out on materials with phenomena that are actually easy for students to observe